Option Volume and Stock Prices: Evidence on Where Informed Traders Trade - Easley, David; O'Hara, Maureen; Srinivas, P.S. (Journal of Finance, 1998)
ABSTRACT This paper investigates the informational role of transactions volume in options markets. We develop an asymmetric information model in which informed traders may trade in option or equity markets. We show conditions under which informed traders trade options, and we investigate the implications of this for the linkage between markets. Our model predicts an important informational role for the volume of particular types of option trades. We empirically test our model's hypotheses with intraday option data. Our main empirical result is that negative and positive option volumes contain information about future stock prices.